Bagaimana Konsep Kapal Selam Diajarkan Secara Sederhana Pada Kurikulum 2013 - Mutia Mutia; Gusti Afifah; Syahrial Ayub (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2018)
Teaching is a teacherÃ¢â¬â¢s daily job. Nevertheless, it turns out that teaching students about how they should study is not easy. This research is included as Research and DevelopmentÃ¢â¬âalso known as RnDÃ¢â¬âwhich aims to give an actual example of how to teach and to embed submarine concept in a simple way through Curriculum 2013. The result of the research, which is a student-oriented learning design which in turn is an implementation of scientific approach, is the output resulted from a long term study, development and experience obtained by the writer team through teaching and training a number of supervisors, school principals, and teachers in various areas of Indonesia. The responses for this teaching model obtained from the teachers have been very positive, whereby 95% teachers claimed that they are very interested in the design, and only 5% claimed that they are mildly interested. This thus indicates that this teaching model can become a model to be referred to in teaching using scientific approach in Curriculum 2013.